Identification of amino acid responsible for the binding of manganese ion in entamoeba histolytica choline kinase - Phang, Simon Hoi Theng (Universiti Sains Malaysia, 2015)
Amoebiasis is an infection by Entamoeba histolytica that causes serious mortality and morbidity cases in developing countries. E. histolytica plasma membrane plays vital roles in survival, ranging from controlling substance movement across the cell to invasiveness of E. histolytica. Phosphatidylcholine (PC) is one of the predominatant phospholipid of the plasma membrane in E. histolytica. PC synthesis begins with the phosphorylation of choline by choline kinase (CK). It is widely accepted that CK from other organisms utilizes magnesium ion (Mg2'r) as cofactor for phosphorylation. Interestingly previous study showed unusual preference in manganese ion (Mg2+) by Entamoeba histolytica choline kinase (EhCK). Hence, this study aims to identify potential amino acid residue responsible for Mn2+ preference. Protein sequence alignment of selected CK and ethanolamine kinase (EK) was done. Glycine-45 residue was selected as a potential amino acid responsible for Mn2+ preference. Gly-45 was replaced by alanine using PCR site directed mutagenesis. Mutant EhCK-G45A was cloned into pGEX-RB vector, expressed and purified. No protein expression by mutant EhCK-G45A was observed. In addition, structural modeling of mutant E11CK-G45A was done. From the model generated Ala-45 resides in the loop region of the model. In conclusion, the study predicted the amino acid that favors Mn2+ binding and also generated EhCK mutant was done to lay the groundwork for future study on EhCK inhibition.